Effects of intermittent catheterization on the nutritional status of patients with dysphagia based on the NRS2002 nutritional assessment (基于NRS2002营养评估的间歇性置管对吞咽障碍患者营养状况的影响) - WANG Yingfen (王迎芬); LI Xia (李侠); JI Danting (纪丹婷); WANG Jirong (王继容) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the effect of intermittent catheterization on the nutritional status of patients with dysphagia based on NRS2002 nutritional assessment. Methods A total of 100 patients with dysphagia were selected as subjects by convenience sampling method. Patients were divided into two groups by random number table method, with 50 patients in each group: control group and observation group. The control group was treated with nasal feeding and routine indwelling method, while the observation group was treated with intermittent catheterization method based on NRS2002 nutritional assessment. The changes of swallowing function and nutritional indexes were compared between the two groups before and after intervention. The incidence of poor prognosis event in the two groups was analyzed. Results After 5 weeks of intervention, the swallowing function rating and the improvement of nutritional status in observation group were significantly better than those in control group (P<0. 05). The incidence of diarrhoea in observation group was significantly lower than that in control group (P<0. 01). Conclusion Interval catheterization based on NRS2002 nutrition assessment can effectively improve the swallowing function of patients, improve nutritional status, and reduce the incidence of poor prognosis. (目的 探讨基于NRS2002营养评估的间歇性置管对吞咽障碍患者营养状况的影响。方法 采用便利抽样法, 选取2018年1月-2021年1月医院神经外科收治的100例吞咽障碍患者为研究对象, 采用随机数字表法将其分成对照组和观察组, 各50例。对照组组采用常规鼻饲留置, 观察组实施基于NRS2002营养评估的间歇性置管法。比较2组患者干预前后吞咽功能、营养学指标的变化情况, 统计2组患者不良预后发生率。结果 干预5周后, 观察组的吞咽功能评级、营养状况改善情况均优于对照组, 差异有统计学意义(P＜0. 05)。观察组腹泻发生率低于对照组, 差异有统计学意义(P＜0. 01)。结论 基于NRS2002营养评估的间歇性置管能有效提高患者的吞咽功能, 改善营养状况, 并降低不良预后发生风险。)